2015
DOI: 10.1017/s0022377815000082
|View full text |Cite
|
Sign up to set email alerts
|

Dust ion acoustic rogue waves in superthermal warm ion plasma

Abstract: The properties of dust ion acoustic rogue waves (DIARWs) in an unmagnetized collisionless plasma system composed of charged dust grains, superthermal electrons and warm ions as a fluid are studied. The multiple scale perturbation method is used to derive a nonlinear Schrödinger equation (NLSE) for DIARWs. From the coefficients of nonlinearity and dispersion, we have determined the critical wave number threshold kcr at which modulational instability sets in. This critical wave number depends on the various plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Abdelsalam [58] studied the nonlinear propagation of solitary and freak waves in a superthermal plasma with positive and negative ions, ion beam and stationary dust particles. More recently, Shalini and Saini [61] have considered the propagation of DIA rogue waves in superthermal plasmas and investigated the combined effects of superthermality and dust concentration on the characteristics of DIA rogue waves.…”
Section: Introductionmentioning
confidence: 99%
“…Abdelsalam [58] studied the nonlinear propagation of solitary and freak waves in a superthermal plasma with positive and negative ions, ion beam and stationary dust particles. More recently, Shalini and Saini [61] have considered the propagation of DIA rogue waves in superthermal plasmas and investigated the combined effects of superthermality and dust concentration on the characteristics of DIA rogue waves.…”
Section: Introductionmentioning
confidence: 99%
“…2005; Paul et al. 2006; Shalini & Saini 2015). It is indeed questionable to treat the heavy ions as Boltzmanian particles in the analyses, as is common practice.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear Schrödinger equation (NLSE) is considered as one of the most useful equations for describing the modulational instability (MI) conditions of different kinds of waves and associated energy re-localization [25,26,27]. Rogue waves (RWs), which are the rational solution of the NLSE [25,26,27], can be observed in super-fluid helium [28], stock-market crashes [29], optics [30,31], and plasma [32,33,34,35]. Kourakis and Shukla [33] studied the MI and localized excitations of DIA Waves (DIAWs).…”
Section: Introductionmentioning
confidence: 99%
“…Kourakis and Shukla [33] studied the MI and localized excitations of DIA Waves (DIAWs). Javidan and Pakzad [34] considered a three-component plasma system having cold inertial ions, super-thermal κ-distributed electrons, and immobile negative dust grains, and studied the MI of DIAWs by using NLSE, and found that the critical wave number for which the DIAWs becomes modulationally unstable decreases with κ. Shalini and Saini [35] investigated on DIA RWs (DIARWs) in a three-component plasma containing inertial warm ion, inertialess κ-distributed electrons, and stationary dust grains, and highlighted that the amplitude of the DIARWs increases with increasing κ. To the best knowledge of the authors, no attempt has been made to study the MI of the DIAWs and associted DI-ARWs in a three-component plasma having inertial warm positive ion and negative dust grain, and inertialess κ-distributed electrons.…”
Section: Introductionmentioning
confidence: 99%